Africa in global agricultural trade - Bouët, Antoine; Cosnard, Lionel; Fall, Cheickh Sadibou (International Food Policy Research Institute, 2019)
It is commonly agreed that trade integration can contribute to the acceleration of economic growth and to poverty alleviation. This is one of the main reasons why African leaders committed at Malabo in 2014 to tripling intra-Africa trade in agricultural commodities and services by 2025. This trade commitment package includes the establishment of a continental free trade area and a continental common external tariff. Its objective is also “to increase and facilitate investment in markets and trade infrastructure” (AUC 2014, 5).